1994
DOI: 10.1007/bf01088428
|View full text |Cite
|
Sign up to set email alerts
|

Consumer acceptability of stiff porridge based on various composite flour proportions of sorghum, maize and cassava

Abstract: A study was conducted to determine consumer acceptable proportions of flours in sorghum (var. serena) and maize or sorghum, maize and cassava composite flours. Breeder's serena flour extracted at 75 percent was mixed at various proportions with maize or with maize and cassava to constitute composite flours. The various composite flours were made into stiff porridge and presented to a group of panellists for sensory evaluation. The evaluation was conducted by scoring on a hedonic scale of 0-5 for poor to excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Although FGD and taste test studies have been conducted to design acceptable formulations of various food products ( 11 17 ) , there are few studies documenting this type of formative research with the purpose of designing a food for an intervention trial. One such study ( 18 ) was conducted in South Africa to assess consumer acceptability of an instant soya–maize porridge compared with an instant plain maize porridge for use in an HIV nutrition intervention trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although FGD and taste test studies have been conducted to design acceptable formulations of various food products ( 11 17 ) , there are few studies documenting this type of formative research with the purpose of designing a food for an intervention trial. One such study ( 18 ) was conducted in South Africa to assess consumer acceptability of an instant soya–maize porridge compared with an instant plain maize porridge for use in an HIV nutrition intervention trial.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous formative research in Kenya (8) demonstrated 'power porridge' was being used as nutrition supplementation among HIV-infected patients, there was lack of data on its optimal formulation and acceptability, the best way to package and transport the supplement, and the best way to monitor consumption. Although FGD and taste test studies have been conducted to design acceptable formulations of various food products (11)(12)(13)(14)(15)(16)(17) , there are few studies documenting this type of formative research with the purpose of designing a food for an intervention trial. One such study (18) was conducted in South Africa to assess consumer acceptability of an instant soya-maize porridge compared with an instant plain maize porridge for use in an HIV nutrition intervention trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings also showed that ugali prepared from maize flour blended with sorghum was consumed by 2%, and 3% consumed ugali prepared from sorghum alone while those consumed ugali made from cassava alone was 5%. Bangu et al [37] observed decrease in consumer acceptability when less 10% of sorghum incorporated to maize. Literature shows food style defines the behaviour of the consumer on food choices [28].…”
Section: Type Of Ugali Commonly Consumed In the Study Areasmentioning
confidence: 99%
“…The blending of cassava and cereal flours is a common practice in urban areas specifically in lake zone [4,10,11]. Ugali produced customarily have improved taste [4,11] and change in prices is relatively low [4].…”
Section: Introductionmentioning
confidence: 99%